THE CONCEPT OF THE PISA INTERNATIONAL ASSESSMENT STUDY AND THE SCIENTIFIC AND CRITICAL ASPECTS OF THE TASKS USED IN IT - Mirzayeva Umidaxon Murodjon qizi; M. B. Artikova (Scholars Digest Publishing, 2024)
As we know, the purpose of the PISA international assessment study is for the countries participating in the study to have an overview of the national education system during the three-year cycle, the effectiveness of the educational reforms carried out over the three-year period, it consists in researching the state of preparation of students for the requirements of society. In the assessment research, not the state of acquisition of evidence-based knowledge of students, but the current state of formation of basic competencies in them is studied.
Keywords: Cycle, national education system, expert, cognitive, basic competence, object of research, opinion, coherence.